Microfluidic chip-based assay for post-hematopoietic stem cell transplantation chimerism monitoring using polymorphic tandem repeat markers - Daud, S.S.; Ibrahim, K.; Choong, S.S.; Vengidasan, L.; Chong, L.A.; Ariffin, H. (Elsevier, 2010)
Following hematopoietic stem cell transplantation (HSCF), it is important to determine whether engraftment is successful and to track the dynamic changes of the graft. Tandem repeats such as minisatellites and microsatellites are currently the most established markers for chimerism application. We have developed a reliable method to quantitatively evaluate engraftment status in post-allogeneic HSCT patients using variable number of tandem repeat (VNTR) markers and ``lab-on-a-chip'' microfluidic electrophoresis technology. Following identification of an informative marker by conventional polymerase chain reaction (PCR), donor chimerism percentage was calculated based on a standard curve generated from artificially mixed patient-donor DNA-specific alleles in serial dilutions. All PCR products were mixed with commercial gel dye and loaded into Agilent DNA 1000 microfluidic LabChips for DNA sizing and quantitation. In 44 patients, separation of pretransplant and donor DNA fragments was resolved clearly and accomplished rapidly within 30 min. Chimerism analysis using this platform is able to detect an amount as low as 6.3% donor DNA with acceptable coefficient of variation values. We also demonstrated concordant chimerism, analysis findings using both microchip tandem repeats and real-time PCR quantitation of insertion-deletion polymorphisms. This microchip platform obviates the need for fluorescently labeled primers or any post-PCR sample manipulation. Quantitative monitoring of post-HSCT chimerism status using microfluidic electrophoresis is a useful tool for both large- and small-scale post-HSCT chimerism centers. (C) 2009 Elsevier Inc. All Fights reserved.